A preparation method for precisely controlling the morphology of UiO-67 materials and application of the prepared materials
By adding specific additives and controlling reaction conditions during the synthesis of UiO-67 material, the diversity of UiO-67 material morphology has been successfully achieved, the problem of single morphology in the existing technology has been solved, and the gas selective separation ability has been improved , and maintains the structural integrity of the material.
Patent Information
- Application Number
- CN202411117808.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-15
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-15
AI Technical Summary
The prior art is difficult to accurately regulate the morphology of UiO-67 materials, resulting in limited catalytic or adsorption properties and failure to achieve morphological diversity on the basis of keeping the structure unchanged.
By adding organic ligands, quaternary ammonium surfactants and proton organic solvents during the synthesis of UiO-67 material, the morphology and particle size of the material are regulated, and ultrasonic and heating reaction processes are used to form spherical, rod-shaped, sheet-shaped, etc. UiO-67 material is characterized by controlling reaction conditions and its structure is retained.
The diversity control of the morphology of UiO-67 material is achieved, the frame structure of the material remains unchanged, and the selective separation ability of paraxylene, orthoxylene and m-xylene gases is improved. The process is simple, the repeatability is good and the ability is capable. Low consumption and no environmental pollution.
Smart Images

Figure CN118652444B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a preparation method for accurately controlling the morphology of a UiO-67 material and application of the prepared material, belonging to the technical field of material preparation. Background Art
[0002] UiO material is a type of metal organic framework material (MOFs), which is composed of metal ions or oxides and organic ligands. UiO-67 is the most representative UiO series material, which has the characteristics of special topological structure, excellent thermal stability and chemical stability, high specific surface area, abundant active sites and adjustable pore structure. It has broad application prospects in the fields of heterogeneous catalysis and gas adsorption separation. UiO-67 materials with different morphologies may have more unique surface properties or structures, affecting their catalytic or adsorption performance. Therefore, the precise control of the morphology of UiO-67 materials has attracted the attention of researchers.
[0003] There are several ways to adjust the morphology of UiO-67 materials: 1) by adding alkaline or acidic regulators to change the pH of the solution to inhibit the growth of crystal faces, thereby forming octahedral UiO-67 materials with larger particles and defects; 2) by adding metal salts to exchange metal cations with UiO-67 materials, some will cause structural collapse and form another morphology MOFs, and some will only undergo cation exchange without changing their own morphology; 3) by introducing other materials to form composite materials with UiO-67 materials, the morphology of UiO-67 materials will be changed, but the structure of UiO-67 materials will change; 4) by calcining UiO-67 materials at high temperatures, the morphology will change, but at high temperatures, the structure of UiO-67 materials will change or even collapse. People's research on the morphology adjustment of UiO-67 materials has stopped here, and UiO-67 materials with different morphologies and unchanged structures have not yet been seen.
[0004] The Chinese invention patent document with publication number CN110003485A discloses a nano UiO-67-NH 2 The method adjusts the particle size of the UiO-67 material by adding a regulator such as glacial acetic acid or triethylamine, and the particle size reaches 90-300nm without involving changes in morphology.
[0005] The Chinese invention patent document with publication number CN109589934A discloses a method for preparing UiO-66 based on benzoic acid regulation and chloroform activation and its adsorption application. The method obtains defective, octahedral UiO-66 by adding benzoic acid as a regulator, and obtains defect-free, octahedral UiO-66 by chloroform activation. This patent is only for obtaining defect-free UiO-66 materials, and is not necessarily applicable to UiO-67 materials, and does not involve the study of morphology and particle size. Summary of the invention
[0006] The technical problem to be solved by the present invention is to provide a preparation method for accurately controlling the morphology of UiO-67 materials and the application of the prepared materials. Aiming at the problem that traditional UiO-67 materials are only octahedral in single morphology, the morphology and particle size of the UiO-67 materials are controlled by adding organic ligands, quaternary ammonium salt surfactants and proton organic solvents in the process of synthesizing the UiO-67 materials. The method has simple process and good repeatability. On the basis of retaining the structure of the UiO-67 material, the octahedral morphology and particle size of the UiO-67 material are changed to produce spherical, rod-shaped and lamellar morphologies. UiO-67 materials with different morphologies have different gas adsorption rates for p-xylene, o-xylene and m-xylene, and can achieve selective separation of gases, and have broad industrial prospects.
[0007] The present invention provides a method for preparing UiO-67 material by precisely controlling its morphology, comprising the following steps:
[0008] (1) Dissolving zirconium oxychloride or hafnium oxychloride, 4,4'-biphenyldicarboxylic acid, 2,2'-biphenyldicarboxylic acid, and a quaternary ammonium salt surfactant in N,N-dimethylformamide to prepare zirconium oxychloride or hafnium oxychloride solution, 4,4'-biphenyldicarboxylic acid solution, 2,2'-biphenyldicarboxylic acid solution, and quaternary ammonium salt surfactant solution; adding a proton organic solvent to the 4,4'-biphenyldicarboxylic acid solution and the 2,2'-biphenyldicarboxylic acid solution to prepare a 4,4'-biphenyldicarboxylic acid mixed solution and a 2,2'-biphenyldicarboxylic acid mixed solution; mixing the zirconium oxychloride or hafnium oxychloride solution, the quaternary ammonium salt surfactant solution, the 4,4'-biphenyldicarboxylic acid mixed solution, and the 2,2'-biphenyldicarboxylic acid mixed solution, performing ultrasonication, and finally transferring the solution to a sealed state for heating and reaction to obtain a solution containing UiO-67 material;
[0009] (2) centrifuging the solution containing UiO-67 material to obtain a first solid; washing and vacuum drying the first solid to obtain a spherical, rod-shaped or sheet-shaped UiO-67 material;
[0010] In the step (1), the mixing order is: 4,4'-biphenyldicarboxylic acid mixed solution and 2,2'-biphenyldicarboxylic acid mixed solution are mixed evenly to obtain a first mixed solution; zirconium oxychloride or hafnium oxychloride solution and quaternary ammonium salt type surfactant solution are mixed evenly to obtain a second mixed solution; and the first mixed solution is added to the second mixed solution.
[0011] Furthermore, in step (1), the quaternary ammonium salt surfactant is hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride or octadecyltrimethylammonium bromide.
[0012] Furthermore, in step (1), the protic organic solvent is methanol, ethanol or ethylene glycol.
[0013] Furthermore, in the step (1), the ratio of the amount of zirconium oxychloride or hafnium oxychloride, 4,4'-biphenyldicarboxylic acid, 2,2'-biphenyldicarboxylic acid, quaternary ammonium salt surfactant, and protic organic solvent to the total volume of zirconium oxychloride or hafnium oxychloride solution, quaternary ammonium salt surfactant solution, 4,4'-biphenyldicarboxylic acid mixed solution and 2,2'-biphenyldicarboxylic acid mixed solution is: 0.08 mmol: 0.08-0.12 mmol: 0.04-0.12 mmol: 0.02-0.1 mmol: 1-4 ml: 11-24 ml.
[0014] Furthermore, in step (1), the ultrasonic conditions are: ultrasonic time 0.5-1h.
[0015] Furthermore, in step (1), the heating reaction conditions are: reaction temperature 100-150° C., reaction time 24-48 h.
[0016] Furthermore, in step (2), the washing conditions are: washing with N,N-dimethylformamide and acetone three to five times respectively; and the vacuum drying conditions are: drying temperature 60-120° C., drying time 10-24 h.
[0017] Another object of the present invention is to provide an application of the UiO-67 material prepared by the above preparation method, comprising the following steps:
[0018] Place spherical, rod-shaped or sheet-shaped UiO-67 material and p-xylene, o-xylene or m-xylene solvent in a gas vapor adsorption analyzer, vacuum activate the UiO-67 material at 120-150°C for 12-24h, then cool the gas vapor adsorption analyzer to room temperature, and then gasify the p-xylene, o-xylene or p-xylene solvent under saturated vapor pressure. The spherical, rod-shaped or sheet-shaped UiO-67 material can achieve saturated adsorption of p-xylene, o-xylene or m-xylene gas at room temperature and 0-100kpa.
[0019] The beneficial effects of the present invention are:
[0020] (1) The method for preparing UiO-67 material morphology by precisely controlling the material morphology of the present invention is simple in process, mild in method, good in repeatability, low in energy consumption, and has no environmental pollution.
[0021] (2) The method for preparing the UiO-67 material with precise control of its morphology can adjust the size of the UiO-67 material by controlling the concentration of organic ligands and the concentration of quaternary ammonium salt surfactant and the reaction time. The size of the UiO-67 material is controlled within 1-2.0 μm. The morphology and uniformity of the UiO-67 material can be affected by controlling the mixing sequence and ultrasound. The UiO-67 material without morphology cannot achieve the selective separation of xylene gases. The addition of different proton organic solvents and quaternary ammonium salt surfactants can be controlled. The UiO-67 material is transformed from the traditional octahedral morphology to spherical, lamellar, and rod-like morphologies in a coordinated manner; when the proton solvent is methanol and the quaternary ammonium salt surfactant coexists, the UiO-67 material morphology is spherical; when the proton solvent is ethanol and the quaternary ammonium salt surfactant coexists, the UiO-67 material morphology is lamellar; when the proton solvent is ethylene glycol and the quaternary ammonium salt surfactant coexists, the UiO-67 material morphology is rod-like; if there is only a proton solvent or a quaternary ammonium salt surfactant, only the particle size of the UiO-67 material can be changed. We used TEM, SEM, XRD, N 2 -BET characterization method found that the morphology of UiO-67 material includes spherical, lamellar and rod-shaped, and did not change the framework structure of UiO-67 material itself.
[0022] (3) The UiO-67 material of the present invention is applied to the field of p-xylene, o-xylene or m-xylene gas adsorption. By utilizing the different morphologies of UiO-67 materials, the adsorption rates of p-xylene, o-xylene or m-xylene gas are different, thereby realizing the separation of xylene gases. The spherical UiO-67 material has a significant adsorption for p-xylene, and can realize the separation of p-xylene and o-xylene or m-xylene gas; the sheet UiO-67 material has a significant adsorption for m-xylene, and can realize the separation of m-xylene and p-xylene or o-xylene; the rod-shaped UiO-67 material has a significant adsorption for o-xylene, and can realize the separation of o-xylene and p-xylene or m-xylene gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a transmission electron microscope (TEM) image of the spherical UiO-67 material obtained in step (2) of Example 1;
[0024] Figure 2 The X-ray diffraction (XRD) diagram of the UiO-67 material obtained in step (2) of Example 1-4 and Comparative Example 1-4;
[0025] Figure 3 The pore size distribution diagram of the NLDFT model of the UiO-67 material obtained in step (2) of Example 1-4 and Comparative Example 1-4 is obtained by nitrogen total adsorption (N) at 77K. 2 -BET) test results;
[0026] Figure 4 This is a gas adsorption test graph of the spherical UiO-67 material obtained in step (2) of Example 1 for p-xylene, o-xylene and m-xylene;
[0027] Figure 5 TEM image of the flaky UiO-67 material obtained in step (2) of Example 2;
[0028] Figure 6 This is a scanning electron microscope (SEM) image of the rod-shaped UiO-67 material obtained in step (2) of Example 3;
[0029] Figure 7 This is a SEM image of the spherical UiO-67 material obtained in step (2) of Example 4;
[0030] Figure 8 TEM image of the UiO-67 material obtained in Comparative Example 1;
[0031] Fig. 9 TEM image of the UiO-67 material obtained in Comparative Example 2;
[0032] Fig.10 TEM image of the UiO-67 material obtained in Comparative Example 3;
[0033] Fig.11 TEM image of the UiO-67 material obtained in Comparative Example 4;
[0034] Fig.12 TEM image of the UiO-67 material obtained in Comparative Example 5;
[0035] Fig.13 This is the TEM image of the UiO-67 material obtained in Comparative Example 6. DETAILED DESCRIPTION
[0036] The present invention is described in detail below in conjunction with embodiments and drawings, but the protection scope of the present invention is not limited thereto. Example 1
[0037] (1) Dissolve 0.08 mmol zirconium oxychloride octahydrate, 0.1 mmol 4,4'-biphenyldicarboxylic acid, 0.1 mmol 2,2'-biphenyldicarboxylic acid, and 0.05 mmol octadecyltrimethylammonium bromide in 4 ml of In N,N-dimethylformamide (hereinafter referred to as DMF), a zirconium oxychloride solution, a 4,4'-biphenyldicarboxylic acid solution, a 2,2'-biphenyldicarboxylic acid solution, and an octadecyltrimethylammonium bromide solution are prepared; then 1.5 ml of methanol is added to the 4,4'-biphenyldicarboxylic acid solution and the 2,2'-biphenyldicarboxylic acid solution to prepare a 4,4'-biphenyldicarboxylic acid mixed solution and a 2,2'-biphenyldicarboxylic acid mixed solution; the 4,4'-biphenyldicarboxylic acid mixed solution and the 2,2'-biphenyldicarboxylic acid mixed solution are mixed evenly to obtain a first mixed solution; the zirconium oxychloride solution and the octadecyltrimethylammonium bromide solution are mixed evenly to obtain a second mixed solution; the first mixed solution is added to the second mixed solution, ultrasonicated for 45 minutes, transferred to a reactor, and reacted at 120° C. for 36 hours to obtain a solution containing UiO-67 material;
[0038] (2) The solution containing the UiO-67 material is centrifuged to obtain a first solid; the first solid is washed four times with N,N-dimethylformamide and acetone respectively, and then vacuum dried at 100° C. for 15 hours to obtain a spherical UiO-67 material.
[0039] The spherical UiO-67 material in step (2) was subjected to transmission electron microscopy (TEM) morphology, X-ray diffraction (XRD) structure, and nitrogen full adsorption (N 2 -BET) pore size distribution characterization test, see Figure 1 , Figure 2 , Figure 3 .
[0040] Depend on Figure 1 It can be seen that the spherical UiO-67 material has a spherical morphology, uniform morphology, and a particle size of about 1 micron; Figure 2 and Figure 3 It can be seen that the structure of the spherical UiO-67 material is consistent with the structure of the traditional UiO-67 material (octahedron), and the pore size distribution of the spherical UiO-67 material is basically consistent with the traditional UiO-67 material (octahedron), indicating that this method is only an adjustment of the morphology and does not involve changes in the framework structure. It is a mild preparation method.
[0041] The spherical UiO-67 material obtained in step (2) is used for the adsorption of p-xylene, o-xylene and m-xylene gases, comprising the following application steps:
[0042] ① Place 25 mg of spherical UiO-67 material and p-xylene, o-xylene or m-xylene solvent into the gas vapor adsorption analyzer;
[0043] ② The spherical UiO-67 material was vacuum activated at 130°C for 18h;
[0044] ③ Cool the gas vapor adsorption analyzer to room temperature, and then gasify the para-xylene or o-xylene or para-xylene solvent under saturated vapor pressure. The spherical UiO-67 material achieves saturated adsorption of para-xylene, o-xylene or m-xylene gas at room temperature and 0-100 kPa;
[0045] ④After the adsorption is completed, repeat step ② to vacuum desorb the adsorbed p-xylene or o-xylene or p-xylene gas;
[0046] ⑤ Place the unadsorbed p-xylene or o-xylene or p-xylene solvent into the gas vapor adsorption analyzer and repeat step ③.
[0047] The spherical UiO-67 material of this embodiment is used for the adsorption of p-xylene, o-xylene and m-xylene gases. The adsorption effect is shown in Figure 4 .
[0048] Depend on Figure 4 It can be seen that the saturated adsorption capacity of p-xylene, m-xylene and o-xylene of spherical UiO-67 material is 49.09 mg / g, 5.066 mg / g and 4.566 mg / g, and the saturated adsorption time is about 615 min. The adsorption gap between p-xylene, m-xylene and o-xylene is 9.69 times and 10.75 times respectively. Therefore, the spherical UiO-67 material has obvious adsorption of xylene gas, and basically has no adsorption of o-xylene and m-xylene gas, and can achieve the separation of p-xylene and o-xylene or m-xylene gas. Example 2
[0049] (1) Dissolve 0.08 mmol zirconium oxychloride octahydrate, 0.08 mmol 4,4'-biphenyldicarboxylic acid, 0.04 mmol 2,2'-biphenyldicarboxylic acid, and 0.02 mmol hexadecyltrimethylammonium bromide in 2.5 ml of In DMF, a zirconium oxychloride solution, a 4,4'-biphenyldicarboxylic acid solution, a 2,2'-biphenyldicarboxylic acid solution, and a hexadecyltrimethylammonium bromide solution are prepared; then 0.5 ml of ethanol is added to each of the 4,4'-biphenyldicarboxylic acid solution and the 2,2'-biphenyldicarboxylic acid solution to prepare a 4,4'-biphenyldicarboxylic acid mixed solution and a 2,2'-biphenyldicarboxylic acid mixed solution; the 4,4'-biphenyldicarboxylic acid mixed solution and the 2,2'-biphenyldicarboxylic acid mixed solution are mixed evenly to obtain a first mixed solution; the zirconium oxychloride solution and the hexadecyltrimethylammonium bromide solution are mixed evenly to obtain a second mixed solution; the first mixed solution is added to the second mixed solution, ultrasonicated for 30 minutes, transferred to a reactor, and reacted at 100° C. for 48 hours to obtain a solution containing UiO-67 material;
[0050] (2) The solution containing the UiO-67 material is centrifuged to obtain a first solid; the first solid is washed three times with N,N-dimethylformamide and acetone respectively, and then vacuum dried at 60° C. for 24 hours to obtain a flaky UiO-67 material.
[0051] The TEM morphology, XRD structure, and N 2 -BET pore size distribution, see Figure 5 , Figure 2 , Figure 3 .
[0052] Depend on Figure 5 It can be seen that the flake UiO-67 material has a flake morphology, uniform morphology, and a particle size of about 2 microns; Figure 2 and Figure 3 It can be seen that the structure of the flake UiO-67 material is consistent with the structure of the traditional UiO-67 material (octahedron), and the pore size distribution of the flake UiO-67 material is basically consistent with the traditional UiO-67 material (octahedron), indicating that this method is only an adjustment of the morphology and does not involve changes in the framework structure. It is a mild preparation method.
[0053] The flaky UiO-67 material obtained in step (2) is used for the adsorption of p-xylene, o-xylene and m-xylene gases, comprising the following application steps:
[0054] ① Place 20 mg of UiO-67 flake material and p-xylene, o-xylene or m-xylene solvent into a gas vapor adsorption analyzer;
[0055] ② Activate the flake UiO-67 material in vacuum at 120°C for 24h;
[0056] ③ Cool the gas vapor adsorption analyzer to room temperature, and then gasify the para-xylene or o-xylene or para-xylene solvent under saturated vapor pressure. The sheet UiO-67 material achieves saturated adsorption of para-xylene, o-xylene or m-xylene gas at room temperature and 0-100 kPa;
[0057] ④After the adsorption is completed, repeat step ② to vacuum desorb the adsorbed p-xylene or o-xylene or p-xylene gas;
[0058] ⑤ Place the unadsorbed p-xylene or o-xylene or p-xylene solvent into the gas vapor adsorption analyzer and repeat step ③.
[0059] The sheet-like UiO-67 material of this embodiment is used for the adsorption of p-xylene, o-xylene and m-xylene gases. The saturated adsorption effect is shown in Table 1.
[0060]
[0061] As shown in Table 1, the flaky UiO-67 material has obvious adsorption for m-xylene gas, but basically has no adsorption for o-xylene and p-xylene gases. The adsorption differences between m-xylene, p-xylene and o-xylene are 10.87 times and 10.41 times, respectively, which can realize the separation of m-xylene and p-xylene or o-xylene gas. Example 3
[0062] (1) Dissolve 0.08 mmol zirconium oxychloride octahydrate, 0.12 mmol 4,4'-biphenyldicarboxylic acid, 0.12 mmol 2,2'-biphenyldicarboxylic acid, and 0.1 mmol hexadecyltrimethylammonium chloride in 5.0 ml of In DMF, a zirconium oxychloride solution, a 4,4'-biphenyl dicarboxylic acid solution, a 2,2'-biphenyl dicarboxylic acid solution, and a hexadecyl trimethyl ammonium chloride solution are prepared; then 2.0 ml of ethylene glycol is added to the 4,4'-biphenyl dicarboxylic acid solution and the 2,2'-biphenyl dicarboxylic acid solution to prepare a 4,4'-biphenyl dicarboxylic acid mixed solution and a 2,2'-biphenyl dicarboxylic acid mixed solution; the 4,4'-biphenyl dicarboxylic acid mixed solution and the 2,2'-biphenyl dicarboxylic acid mixed solution are mixed evenly to obtain a first mixed solution; the zirconium oxychloride solution and the hexadecyl trimethyl ammonium chloride solution are mixed evenly to obtain a second mixed solution; the first mixed solution is added to the second mixed solution, ultrasonicated for 60 minutes, transferred to a reactor, and reacted at 150° C. for 24 hours to obtain a solution containing UiO-67 material;
[0063] (2) The solution containing the UiO-67 material is centrifuged to obtain a first solid; the first solid is washed with N,N-dimethylformamide and acetone five times respectively, and then vacuum dried at 120° C. for 10 hours to obtain a rod-shaped UiO-67 material.
[0064] The rod-shaped UiO-67 material in step (2) was subjected to scanning electron microscopy (SEM) morphology, XRD structure, and N 2 -BET pore size distribution, see Figure 6 , Figure 2 , Figure 3 .
[0065] Depend on Figure 6 It can be seen that the rod-shaped UiO-67 material has a rod-shaped morphology, a uniform morphology, and a particle size of about 1.3 microns; Figure 2 and Figure 3 It can be seen that the structure of the rod-shaped UiO-67 material is consistent with the structure of the traditional UiO-67 material (octahedron), and the pore size distribution of the rod-shaped UiO-67 material is basically consistent with the traditional UiO-67 material (octahedron), indicating that this method is only an adjustment of the morphology and does not involve changes in the framework structure. It is a mild preparation method.
[0066] The rod-shaped UiO-67 material obtained in step (2) is used for the adsorption of p-xylene, o-xylene and m-xylene gases, comprising the following application steps:
[0067] ① Place 30 mg of rod-shaped UiO-67 material and p-xylene, o-xylene or m-xylene solvent into the gas vapor adsorption analyzer;
[0068] ② The rod-shaped UiO-67 material was vacuum activated at 150°C for 12h;
[0069] ③ Cool the gas vapor adsorption analyzer to room temperature, and then gasify the para-xylene or o-xylene or para-xylene solvent under saturated vapor pressure. The rod-shaped UiO-67 material achieves saturated adsorption of para-xylene, o-xylene or m-xylene gas at room temperature and 0-100 kPa;
[0070] ④After the adsorption is completed, repeat step ② to vacuum desorb the adsorbed p-xylene or o-xylene or p-xylene gas;
[0071] ⑤ Place the unadsorbed p-xylene or o-xylene or p-xylene solvent into the gas vapor adsorption analyzer and repeat step ③.
[0072] The rod-shaped UiO-67 material of this embodiment is used for the adsorption of p-xylene, o-xylene and m-xylene gases. The saturated adsorption effect is shown in Table 2.
[0073]
[0074] As shown in Table 2, the rod-shaped UiO-67 material has obvious adsorption for o-xylene gas, but basically has no adsorption for p-xylene and m-xylene gas. The adsorption differences between o-xylene, p-xylene and m-xylene are 11.39 times and 10.88 times, respectively, which can realize the separation of o-xylene and p-xylene or m-xylene gas. Example 4
[0075] (1) Dissolve 0.08 mmol of hafnium oxychloride octahydrate, 0.12 mmol of 4,4'-biphenyldicarboxylic acid, 0.12 mmol of 2,2'-biphenyldicarboxylic acid, and 0.8 mmol of octadecyltrimethylammonium bromide in 4.0 ml of In DMF, a hafnium oxychloride solution, a 4,4'-biphenyldicarboxylic acid solution, a 2,2'-biphenyldicarboxylic acid solution, and an octadecyltrimethylammonium bromide solution are prepared; then 1.5 ml of methanol is added to the 4,4'-biphenyldicarboxylic acid solution and the 2,2'-biphenyldicarboxylic acid solution to prepare a 4,4'-biphenyldicarboxylic acid mixed solution and a 2,2'-biphenyldicarboxylic acid mixed solution; the 4,4'-biphenyldicarboxylic acid mixed solution and the 2,2'-biphenyldicarboxylic acid mixed solution are mixed evenly to obtain a first mixed solution; the hafnium oxychloride solution and the octadecyltrimethylammonium bromide solution are mixed evenly to obtain a second mixed solution; the first mixed solution is added to the second mixed solution, ultrasonicated for 45 minutes, transferred to a reactor, and reacted at 120° C. for 36 hours to obtain a solution containing UiO-67 material;
[0076] (2) The solution containing the UiO-67 material is centrifuged to obtain a first solid; the first solid is washed with N,N-dimethylformamide and acetone five times respectively, and then vacuum dried at 120° C. for 15 hours to obtain a spherical UiO-67 material.
[0077] The spherical UiO-67 material in step (2) was subjected to SEM morphology, XRD structure, and N 2 -BET pore size distribution, see Figure 7 , Figure 2 , Figure 3 .
[0078] Depend on Figure 1 and Figure 7 By comparison, it can be seen that changing the concentration of the reactants can adjust the particle size of the spherical UiO-67 material, and the particle size changes from 1 micron to 1.2 microns; Figure 2 and Figure 3It can be seen that the structure of the spherical UiO-67 material is consistent with the structure of the traditional UiO-67 material (octahedron), and the pore size distribution of the spherical UiO-67 material is basically consistent with the traditional UiO-67 material (octahedron). Therefore, the metal cation precursors of hafnium oxychloride and zirconium oxychloride do not change the framework structure and morphology of the spherical UiO-67 material.
[0079] The spherical UiO-67 material obtained in step (2) is used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the test method is the same as that in Example 1.
[0080] The spherical UiO-67 material of this embodiment is used for the adsorption of p-xylene, o-xylene and m-xylene gases. The saturated adsorption effect is shown in Table 3.
[0081]
[0082] From Table 3 and Figure 4 By comparison, the spherical UiO-67 material has obvious adsorption of p-xylene gas, but basically has no adsorption of m-xylene and o-xylene gases. The adsorption differences between p-xylene, m-xylene and o-xylene are 10.19 times and 9.42 times, respectively. The separation of p-xylene from o-xylene or m-xylene gas can be achieved. In addition, the particle size of the same morphology has little effect on the saturated adsorption capacity, or basically no effect, but it will affect the adsorption rate, and the adsorption rate of smaller particles is faster. Comparative Example 1
[0083] Comparative Example 1 is the same as step (2) of Example 1, except that no 2,2'-biphenyldicarboxylic acid, octadecyltrimethylammonium bromide and methanol are added in step (1).
[0084] The steps of step (1) are as follows:
[0085] 0.08 mmol zirconium oxychloride octahydrate and 0.1 mmol 4,4'-biphenyldicarboxylic acid were dissolved in 8 ml DMF respectively to prepare zirconium oxychloride solution and 4,4'-biphenyldicarboxylic acid solution; then the zirconium oxychloride solution was added to the 4,4'-biphenyldicarboxylic acid solution, ultrasonicated for 45 minutes, transferred to a reactor, reacted at 120°C for 36 hours, and obtained a solution containing UiO-67 material.
[0086] In step (2), the UiO-67 material was subjected to TEM morphology, XRD structure, and N 2 -BET pore size distribution, see Figure 8 , Figure 2 , Figure 3 .
[0087] Depend on Figure 8It can be seen that the UiO-67 material of Comparative Example 1 has an octahedral morphology and a particle size of about 60 nm. Figure 1 and Figure 8 By comparison, the addition of organic ligand solution, quaternary ammonium salt surfactant solution and proton organic solvent can change the morphology and particle size of UiO-67 material. Figure 2 and Figure 3 It can be seen that the addition of organic ligand solution, quaternary ammonium salt surfactant solution and proton organic solvent cannot change the XRD structure and pore size of UiO-67 material.
[0088] The UiO-67 material obtained in step (2) was used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the test method was the same as that in Example 1.
[0089] The UiO-67 material of this comparative example is used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the saturated adsorption effect is shown in Table 4. Comparative Example 2
[0090] Comparative Example 2 is the same as step (2) of Example 1, except that no methanol is added in step (1).
[0091] The TEM morphology, XRD structure, and N 2 -BET pore size distribution, see Fig. 9 , Figure 2 , Figure 3 .
[0092] Depend on Fig. 9 It can be seen that the UiO-67 material of Comparative Example 2 has an octahedral morphology and a particle size of about 800 nm; Figure 1 and Figure 8 as well as Fig. 9 By comparison, the addition of organic ligand solution and quaternary ammonium salt surfactant solution cannot change the morphology of UiO-67 material, but can change the particle size; Figure 2 and Figure 3 It can be seen that the addition of organic ligand solution and quaternary ammonium salt surfactant solution cannot change the XRD structure and pore size of UiO-67 material.
[0093] The UiO-67 material obtained in step (2) was used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the test method was the same as that in Example 1.
[0094] The UiO-67 material of this comparative example is used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the saturated adsorption effect is shown in Table 4. Comparative Example 3
[0095] Comparative Example 3 is the same as step (2) of Example 1, except that no quaternary ammonium salt surfactant is added in step (1).
[0096] The TEM morphology, XRD structure, and N 2 -BET pore size distribution, see Fig.10 , Figure 2 , Figure 3 .
[0097] Depend on Fig.10 It can be seen that the UiO-67 material of Comparative Example 3 has an octahedral morphology and a particle size of about 800 nm; Figure 1 , Figure 8 , Fig. 9 , Fig.10 By comparison, the addition of organic ligand solution and proton organic solvent cannot change the morphology of UiO-67 material, but can change the particle size. Therefore, quaternary ammonium salt surfactant and proton organic solvent are the key to change the morphology of UiO-67 material. Figure 2 and Figure 3 It can be seen that the addition of organic ligand solution and proton organic solvent cannot change the XRD structure and pore size of UiO-67 material.
[0098] The UiO-67 material obtained in step (2) was used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the test method was the same as that in Example 1.
[0099] The UiO-67 material of this comparative example is used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the saturated adsorption effect is shown in Table 4. Comparative Example 4
[0100] Comparative Example 4 is the same as step (2) of Example 1, except that no quaternary ammonium salt surfactant and 2,2'-biphenyldicarboxylic acid are added in step (1).
[0101] The TEM morphology, XRD structure, and N 2 -BET pore size distribution, see Fig.11 , Figure 2 , Figure 3 .
[0102] Depend on Fig.11 It can be seen that the UiO-67 material of Comparative Example 4 has an octahedral morphology and a particle size of about 220 nm; Figure 1 , Figure 8 , Fig.11 By comparison, the addition of proton organic solvents cannot change the morphology of UiO-67 materials, but can change the size of particles. Figure 2and Figure 3 It can be seen that the addition of protic organic solvents cannot change the XRD structure and pore size of UiO-67 materials.
[0103] The UiO-67 material obtained in step (2) was used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the test method was the same as that in Example 1.
[0104] The UiO-67 material of this comparative example is used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the saturated adsorption effect is shown in Table 4. Comparative Example 5
[0105] Comparative Example 5 is the same as step (2) of Example 1, except that the mixing order in step (1) is different. The 4,4'-biphenyldicarboxylic acid mixed solution and the zirconium oxychloride solution are mixed evenly to obtain a first mixed solution; the 2,2'-biphenyldicarboxylic acid mixed solution and the octadecyltrimethylammonium bromide solution are mixed evenly to obtain a second mixed solution.
[0106] The TEM morphology of the UiO-67 material in step (2) is characterized as shown in Fig.12 .
[0107] Depend on Fig.12 It can be seen that the morphology of UiO-67 material is poor and uneven, and different mixing orders will affect the morphology and uniformity of UiO-67 material.
[0108] The UiO-67 material obtained in step (2) was used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the test method was the same as that in Example 1.
[0109] The UiO-67 material of this comparative example is used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the saturated adsorption effect is shown in Table 4. Comparative Example 6
[0110] Comparative Example 6 is the same as step (2) of Example 1, except that in step (1), ultrasound is replaced by stirring.
[0111] The TEM morphology of the UiO-67 material in step (2) is characterized as shown in Fig.13 .
[0112] Depend on Fig.13 It can be seen that the morphology of UiO-67 material is poor and uneven, and ultrasound will affect the morphology and uniformity of UiO-67 material.
[0113] The UiO-67 material obtained in step (2) was used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the test method was the same as that in Example 1.
[0114] The UiO-67 material of this comparative example is used for the adsorption of p-xylene, o-xylene and m-xylene gases, and the saturated adsorption effect is shown in Table 4.
[0115]
[0116] It can be seen from Table 4 that the traditional octahedral UiO-67 materials (Comparative Example 1, Comparative Example 2, Comparative Example 3, Comparative Example 4) and the non-morphological UiO-67 materials (Comparative Example 5 and Comparative Example 6) cannot achieve the selective separation of p-xylene, o-xylene and m-xylene gases. The UiO-67 materials with different morphologies have different adsorption rates for xylene gases, and can achieve the separation of p-xylene, o-xylene and m-xylene gases.
[0117] By comparing comparative examples 1-6 with Example 1, it is found that the addition of organic ligand solution, quaternary ammonium salt surfactant solution and proton organic solvent can change the particle size of UiO-67 material, but cannot change the XRD structure and pore size of UiO-67 material. Proton organic solvent and quaternary ammonium salt surfactant are the key to cause morphological changes, and the two have a synergistic effect. When the proton solvent is methanol and the quaternary ammonium salt surfactant coexists, the UiO-67 material morphology is spherical; when the proton solvent is ethanol and the quaternary ammonium salt surfactant coexists, the UiO-67 material morphology is flaky; when the proton solvent is ethylene glycol and the quaternary ammonium salt surfactant coexists, the UiO-67 material morphology is rod-shaped; if there is only proton solvent or quaternary ammonium salt surfactant, the particle size of UiO-67 material can only be changed. Mixing order and ultrasound will affect the morphology and uniformity of UiO-67 material, and then affect the separation effect of xylene gas.
[0118] The gas vapor adsorption analyzer in the embodiment of the present invention comes from Best, and is composed of a programmed temperature module, a gas path device, a vacuum pump, a molecular pump, a vacuum system, a temperature measurement module, a pressure measurement module, a temperature control module, a microbalance, a flow meter, etc.; temperature range: room temperature-400ºC; weighing range: 10-1000mg (0.1ug: 10-100mg); model is BSD-VVS.
[0119] The above description is only a preferred embodiment of the present invention and cannot limit the scope of the present invention. That is, equivalent changes and modifications described in the scope of the present invention and the description should all fall within the scope of the present invention.
Claims
1. A preparation method for precisely controlling the morphology of UiO-67 materials. It is characterized in that The following steps are involved: (1) Dissolving zirconium oxychloride or hafnium oxychloride, 4,4'-biphenyldicarboxylic acid, 2,2'-biphenyldicarboxylic acid, and a quaternary ammonium salt surfactant in N,N-dimethylformamide to prepare zirconium oxychloride or hafnium oxychloride solution, 4,4'-biphenyldicarboxylic acid solution, 2,2'-biphenyldicarboxylic acid solution, and quaternary ammonium salt surfactant solution; adding a proton organic solvent to the 4,4'-biphenyldicarboxylic acid solution and the 2,2'-biphenyldicarboxylic acid solution to prepare a 4,4'-biphenyldicarboxylic acid mixed solution and a 2,2'-biphenyldicarboxylic acid mixed solution; mixing the zirconium oxychloride or hafnium oxychloride solution, the quaternary ammonium salt surfactant solution, the 4,4'-biphenyldicarboxylic acid mixed solution, and the 2,2'-biphenyldicarboxylic acid mixed solution, performing ultrasonication, and finally transferring the solution to a sealed state for heating and reaction to obtain a solution containing UiO-67 material; (2) centrifuging the solution containing UiO-67 material to obtain a first solid; washing and vacuum drying the first solid to obtain a spherical, rod-shaped or sheet-shaped UiO-67 material; In the step (1), the mixing order is: 4,4'-biphenyldicarboxylic acid mixed solution and 2,2'-biphenyldicarboxylic acid mixed solution are mixed evenly to obtain a first mixed solution; zirconium oxychloride or hafnium oxychloride solution and quaternary ammonium salt type surfactant solution are mixed evenly to obtain a second mixed solution; the first mixed solution is added to the second mixed solution; In the step (1), the quaternary ammonium salt surfactant is hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride or octadecyltrimethylammonium bromide; In the step (1), the protic organic solvent is methanol, ethanol or ethylene glycol; In the step (1), the ratio of the amount of zirconium oxychloride or hafnium oxychloride, 4,4'-biphenyldicarboxylic acid, 2,2'-biphenyldicarboxylic acid, quaternary ammonium salt surfactant, and protic organic solvent to the total volume of zirconium oxychloride or hafnium oxychloride solution, quaternary ammonium salt surfactant solution, 4,4'-biphenyldicarboxylic acid mixed solution and 2,2'-biphenyldicarboxylic acid mixed solution is: 0.08mmol: 0.08-0.12mmol: 0.04-0.12mmol: 0.02-0.1mmol: 1-4ml: 11-24ml.
2. The method for preparing the UiO-67 material morphology by precisely controlling the UiO-67 material morphology according to claim 1, It is characterized in that In the step (1), the ultrasonic conditions are: ultrasonic time 0.5-1h.
3. The method for preparing the UiO-67 material morphology by precisely controlling the UiO-67 material morphology according to claim 1, It is characterized in that In the step (1), the heating reaction conditions are: reaction temperature 100-150° C., reaction time 24-48 h.
4. The method for preparing the UiO-67 material morphology by precisely controlling the UiO-67 material morphology according to claim 1, It is characterized in that In the step (2), the washing conditions are: washing with N,N-dimethylformamide and acetone three to five times respectively; the vacuum drying conditions are: drying temperature 60-120° C., drying time 10-24 h.
5. Application of the UiO-67 material prepared by the preparation method according to any one of claims 1 to 4, It is characterized in that The steps include: Place spherical, rod-shaped or sheet-shaped UiO-67 material and p-xylene, o-xylene or m-xylene solvent in a gas vapor adsorption analyzer, vacuum activate the UiO-67 material at 120-150°C for 12-24h, then cool the gas vapor adsorption analyzer to room temperature, and then gasify the p-xylene, o-xylene or m-xylene solvent under saturated vapor pressure. The spherical, rod-shaped or sheet-shaped UiO-67 material can achieve saturated adsorption of p-xylene, o-xylene or m-xylene gas at room temperature and 0-100kpa.
Citation Information
Patent Citations
Method for preparing UiO-66 based on benzoic acid regulation and chloroform activation and adsorption application
CN109589934A
Nano UiO-67-NH2 as well as preparation method and application thereof
CN110003485A
Preparation method of ZIF-8 photonic crystal sensor
CN109696420A
Synthesis method of sheet-assembled rod-like MOF-74(Mn)
CN110898855A
Metal organic framework adsorbent for xylene separation as well as preparation method and application of metal organic framework adsorbent
CN115073761A
